О вычислении некоторых сингулярных интегралов - Литвин, А.И.; Симонженков, С.Д.; Коваленко, И.Л. (Український математичний журнал, 1993)
A method for the approximate calculation of Cauchy-type integrals with logarithmic singularities is proposed. It is based on the expansion of a functionf(t) in a series in the Chebyshev polynomials.